Development of Android-Based Interactive Media Articulate Storyline 3 in IPAS Subjects Fourth Grade - Auvisena, Arlinta Ulfa; Fathurrahman, Moh. (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to develop educational materials using Articulate Storyline, an e-learning software known for its practicality in creating interactive learning materials. This program is very helpful because it has an intuitive and easy-to-operate interface, which allows teachers and curriculum creators to design materials without requiring special skills in programming or graphic design. The methodology used in this study is Research and Development (R&D), following the ADDIE model which includes analysis, design, development, implementation, and evaluation. Data collection involves both test and non-test methods, and data is analyzed through quantitative as well as qualitative approaches. The results showed that the use of Articulate Storyline is very effective in learning natural and social sciences for grade IV students. This is evident from the high assessment by material and media experts, respectively by 91% and 90%. A significant increase in test scores from 55 to 80 and an increase in students' n-gain of 0.57 demonstrate the effectiveness of this tool in the teaching and learning process. Thus, Articulate Storyline is considered an ideal and effective tool for interactive learning in grade IV science subjects.